2019
DOI: 10.33689/spormetre.521555
|View full text |Cite
|
Sign up to set email alerts
|

Serbest Zaman Doyumu, Serbest Zamanda Sikilma Algisi Ve İş Tatmi̇ni̇ İli̇şki̇si̇: Akademi̇syenler Üzeri̇ne Bi̇r Araştirma

Abstract: Öz: Bu çalışmanın amacı, akademisyenlerin serbest zaman doyumu, serbest zamanda sıkılma algısı ve iş tatmin düzeylerindeki farklılıkları ortaya koymaktır. Aynı zamanda, serbest zaman doyumunun ve serbest zamanda sıkılma algısının katılımcıların iş tatminlerini yordama gücünü belirlemektir. Çalışmanın örneklem grubunu 129 kadın ve 118 erkek akademisyen oluşturmuştur. Katılımcılar "Serbest Zaman Doyum Ölçeği-SZDÖ" (Gökçe ve Orhan, 2011), "Serbest Zamanda Sıkılma Algısı Ölçeği-SZSAÖ" (Kara ve ark., 2014) ve "Minn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 26 publications
1
7
0
3
Order By: Relevance
“…However, the main effect of genders on the sub-dimensions of the LSS was not significant, except for the significant differences in the "Educational," "Social," "Physical," and "Relaxation" sub-dimensions, which suggests that women were more satisfied than men in educational, social, physical, and relaxation aspects of leisure activities. In the literature, Doğan et al (2019), Sönmezoğlu et al (2014), Serdar and Demirel (2020), Serdar and Ay (2016) and Serdar et al (2018) reaches similar results. When the SAS-SV scores were according to the gender variable, it was determined that females were more addicted to smartphones than males.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…However, the main effect of genders on the sub-dimensions of the LSS was not significant, except for the significant differences in the "Educational," "Social," "Physical," and "Relaxation" sub-dimensions, which suggests that women were more satisfied than men in educational, social, physical, and relaxation aspects of leisure activities. In the literature, Doğan et al (2019), Sönmezoğlu et al (2014), Serdar and Demirel (2020), Serdar and Ay (2016) and Serdar et al (2018) reaches similar results. When the SAS-SV scores were according to the gender variable, it was determined that females were more addicted to smartphones than males.…”
Section: Discussionmentioning
confidence: 57%
“…Leisure boredom generally stem from the monotonous assessment of activities in time (Shaw et al, 1996;Yaşartürk et al, 2017). Participating in activities, which can create awareness for individuals in evaluating their leisure and provide more satisfaction with varying activities, can minimize the perception of boredom (Doğan et al, 2019). In other words, Iso-Ahola and Weissinger (1990) have emphasized that the perception of leisure boredom arises when leisure experiences do not meet people's expectations and needs, and it is important to experience satisfaction in leisure occupation to minimize feelings of boredom (Kil et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…However, there are other studies indicating no significant differences related to internet addiction in terms of gender variable (28,29). Doğan (30) and Kara and Ayverdi (31) stated significant differences in favor of male participants for boredom subscale of LBS in their studies whereas Kara (32) and Wegner (33) stated that the significant differences are in favor of female participants.…”
Section: Discussionmentioning
confidence: 90%
“…On the other hand, there are studies showing significant differences in the boredom and dissatisfaction subscales in terms of participation in physical activity or exercise in leisure variable. The studies in the literature reported that individuals who do not participate in physical activity or exercise had higher mean scores from the subscales (37,30). In the research carried out by Kara et.al.…”
Section: Discussionmentioning
confidence: 99%
“…Serbest zamanlarda düzenli olarak egzersize katılım, bireylere hem fizyolojik hem de sosyo-psikolojik anlamda fayda sağlamaktadır (Cuthbert, King-Shier, Ruether, Tapp, Wytsma-Fisher, Fung, ve Culos-Reed, 2018;Doğan, 2021;Elçi ve diğerleri, 2019;Gürbüz, 2017;Ito ve diğerleri, 2018;Knapen ve diğerleri, 2015). Ancak uygulanan egzersizlerin türü, şiddeti, süresi ve hangi sıklıkta yapıldığı, fayda sağlama noktasında iyi analiz edilmelidir.…”
Section: Introductionunclassified